2005
DOI: 10.1089/vbz.2005.5.276
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fungal Isolates for Development of a Myco-Acaricide for Cattle Tick Control

Abstract: Entomopathogenic fungal isolates of Arachnid origin were assessed for their ability to produce mortality and inhibit egg hatching in Boophilus microplus with the aim of selecting an isolate for development into a myco-acaricide for control of cattle ticks. The ability of the most promising isolate to target developmental stages of more than one tick species and the optimum concentration of fungal inoculum to be used for future studies were determined. Metarhizium anisopliae was the most pathogenic of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…The genus Simplicillium presently consists of three species: Simplicillium lanosoniveum, Simplicillium obclavatum and Simplicillium lamellicola (Nonaka et al, 2013). Some studies reported that S. lamellicola was used to control ticks (Polar et al, 2005), Heterodera glycines Ichinohe cysts and Meloidogyne arenaria eggs (Gams, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Simplicillium presently consists of three species: Simplicillium lanosoniveum, Simplicillium obclavatum and Simplicillium lamellicola (Nonaka et al, 2013). Some studies reported that S. lamellicola was used to control ticks (Polar et al, 2005), Heterodera glycines Ichinohe cysts and Meloidogyne arenaria eggs (Gams, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Infection by this fungus results from direct penetration of the cuticle, using a combination of enzymic and physical mechanisms, without any requirement for injection or specialized mode of entry. Strains of M. anisopliae have been shown to be pathogenic towards members of the 'soft tick' Argasidae family such as the tick fowl Argas persicargas, as well as numerous members of the 'hard tick' Ixodidae family (Kaaya & Hassan, 2000;Polar et al, 2005;Samish et al, 2004;Sewify & Habib, 2001). These include tick species from a wide range of genera that are of economic, medical and veterinary importance such as Amblyomma, Rhipicephalus (Boophilus) and Ixodes (Fernandes et al, 2003;Kirkland et al, 2004b;Pirali-Kheirabadi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…With the grasshopper Locustana pardalina, the preferred hemolymph thermoregulation set point is 38-41 °C and the maximum hemolymph temperature is 47.4 °C [1]. Insect-host environments also inhibit conidial germination and reduce mycelial growth in the hemolymph of infected insects, e.g., the host temperatures in sunlight of the sheep mite is 37 °C [2] and 41-45 °C for cattle ticks [3][4][5][6]. Therefore, the high temperatures found in some insect environments may be sufficiently high to impede growth of many insect-pathogenic fungi.…”
mentioning
confidence: 99%